2019
DOI: 10.3389/fpsyg.2019.02637
|View full text |Cite
|
Sign up to set email alerts
|

What Do Adolescents See on Social Media? A Diary Study of Food Marketing Images on Social Media

Abstract: Food marketing influences eating preferences and choices, especially among adolescents, contributing to the rise of overweight, obesity, and other chronic health disorders. Recent social media advancements have provided food marketers with platforms to reach out to many in more personal and authentic ways as compared to classical media advertising. Such personalized and borderless social media platforms allow marketers to easily use owned, paid, and earned (word-of –mouth) marketing strategies, including paid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
117
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 41 publications
11
117
0
2
Order By: Relevance
“…Advertisers have extensive digital media presence including on social and media-sharing platforms where they promote products and brands as exciting and interactive [6,10,11]. In digital media (as in traditional media), most food and beverage advertising is for unhealthy items: reports indicate 65%-80% of food advertising online is for HFSS products or brands associated with these foods [12][13][14]. Furthermore, as food and beverage companies have extensive followings online, including among teens, their activities reach large audiences [15]; the food brands with the greatest potential reach amongst teens are almost all brands with many or mostly unhealthy products in their portfolios [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advertisers have extensive digital media presence including on social and media-sharing platforms where they promote products and brands as exciting and interactive [6,10,11]. In digital media (as in traditional media), most food and beverage advertising is for unhealthy items: reports indicate 65%-80% of food advertising online is for HFSS products or brands associated with these foods [12][13][14]. Furthermore, as food and beverage companies have extensive followings online, including among teens, their activities reach large audiences [15]; the food brands with the greatest potential reach amongst teens are almost all brands with many or mostly unhealthy products in their portfolios [16].…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents are at risk of exposure to unhealthy food advertising because of their very high levels of Internet and social media usage. Diary, screen-recording and avatar studies indicate high levels of exposure [12,14,17]. However, evidence for how young people engage with and respond to food advertising in digital media remains limited [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…Cancers and cardiovascular diseases are examples of civilizational diseases related to population lifestyles and social contexts. The media could better support these healthier campaigns [ 145 ], considering its influence on adolescents [ 146 ], for example, in terms of food choices [ 147 ].…”
Section: Literature Surveymentioning
confidence: 99%
“…In one small study, 21 Belgian adolescents age 12-18 years were instructed to take screenshots of foodrelated images they encountered on social media. 49 They reported that 67% of the images exclusively depicted unhealthy food such as soft drinks, fried foods, and sweets, and almost half of the images depicted branded food products. Of the branded food images, half appeared as unpaid word-ofmouth marketing but were suspected to be paid marketing efforts.…”
Section: Social Media and Marketingmentioning
confidence: 99%